2015
DOI: 10.1117/12.2177390
|View full text |Cite
|
Sign up to set email alerts
|

Advances in sublimation studies for particles of explosives

Abstract: When handling explosives, or related surfaces, the hands routinely become contaminated with particles of explosives and related materials. Subsequent contact with a solid surface results in particle crushing and deposition. These particles provide an evidentiary trail which is useful for security applications. As such, the opto-physico-chemical characteristics of these particles are critical to trace explosives detection applications in DOD or DHS arenas. As the persistence of these particles is vital to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…To a first approximation, the sublimation results for DNT can be applied to TNT or other explosives by using a relative vapor pressure correction factor. Our previous report confirmed that, as expected, increasing airflow resulted in increased sublimation rates, as vapor molecules removed from near the surface of the particle increased the net flux of molecules escaping the surface layer 12 . We discovered a linear relationship between the airspeed and a particle-size-independent term we defined as the radial sublimation velocity (RSV), which is defined in the following section.…”
Section: Particulate Sources Of Explosives and Their Characteristicssupporting
confidence: 58%
See 4 more Smart Citations
“…To a first approximation, the sublimation results for DNT can be applied to TNT or other explosives by using a relative vapor pressure correction factor. Our previous report confirmed that, as expected, increasing airflow resulted in increased sublimation rates, as vapor molecules removed from near the surface of the particle increased the net flux of molecules escaping the surface layer 12 . We discovered a linear relationship between the airspeed and a particle-size-independent term we defined as the radial sublimation velocity (RSV), which is defined in the following section.…”
Section: Particulate Sources Of Explosives and Their Characteristicssupporting
confidence: 58%
“…The persistence, or lifetime, of particles of explosives on a surface is a limiting factor for security applications. A range of environmental parameters and particle properties, shown in Figure 1, influence particle sublimation including: inherent chemical vapor pressure, particle size and geometry, airflow, substrate topography, relative humidity, reactivity, adlayers, admixtures, particle areal density and temperature [9][10][11][12] . In a previous work 12 , we have specifically studied the effects of areal coverage, airflow velocity and particle field size on sublimation of 2,4-dinitrotoluene (DNT) particles on glass substrates.…”
Section: Particulate Sources Of Explosives and Their Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations